2014
DOI: 10.2478/botcro-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Deficiency and Potassium Application on Plant Growth, Osmolytes and Grain Yield of Brassica Napus Cultivars

Abstract: -One of the major issues with brassica oil seed production is the water requirement of the brassica crop. To address the problem, fi eld experiments were conducted to evaluate the effect of potassium (K) and water defi ciency levels on canola (Brassica napus L.). Analysis of the data revealed that application of K, irrigation and interactions between irrigation and cultivar (I × C), irrigation and potassium (I × K), potassium and cultivar (K × C), and irrigation and cultivar and potassium (I × C × K) had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…6a and b). This result is in agreement with the work of Ali et al (2014) who reported that water deficiency resulted in an increase in the accumulation of reducing sugar in Brassica napus. Polythelene glycol of 10 to 30%, increased total sugar content in the root of rice seedlings from 24 to 72 hrs of application and 20% PEG increased total sugar content in the root by 20.0 and 50.13% at 24 and 72 hrs of treatment, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6a and b). This result is in agreement with the work of Ali et al (2014) who reported that water deficiency resulted in an increase in the accumulation of reducing sugar in Brassica napus. Polythelene glycol of 10 to 30%, increased total sugar content in the root of rice seedlings from 24 to 72 hrs of application and 20% PEG increased total sugar content in the root by 20.0 and 50.13% at 24 and 72 hrs of treatment, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Polyethylene glycol generated osmotic stress decreased the chlorophyll content in Thymus vulgaris (Razavizadeh et al 2019). Water deficiency increased sugar accumulation in Brassica napus (Ali et al 2014). Due to water stress a significant increase in proline content was observed in sweet basil (Al-Huqail et al 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Zhang et al [125] observed that exogenous K applications increase the Pro content in Z. mays cultivars under drought conditions. At the same time, Ali et al [126] reported that under drought stress, K applications increase the shoot Pro content in B. napus in a dose-dependent manner. Similarly, Zahoor et al [127] found that K application generates the Pro content in G. hirsutum during drought stress.…”
Section: Droughtmentioning
confidence: 94%
“…The resistance of cultivars to biotic and abiotic stresses is particularly important (Khalil et al, 2022). This problem was undertaken among others by Ali et al (2014) who proved a significant effect of oilseed rape cultivar on water deficit stress. These authors also showed a significant differentiation of yields of the assessed cultivars as a result of the use of a factor limiting the stress of water shortage, i.e.…”
Section: Introductionmentioning
confidence: 99%